Up-conversion luminescence lifetime thermometry based on the 1G4 state of Tm3+ modulated by cross relaxation processes. Issue 42 (15th October 2019) - Fu, Yuting; Zhao, Lijuan; Guo, Yuao; Yu, Hua
Abstract : The first study on the up-conversion luminescence lifetime thermometry based on the 1 G4 state of Tm 3+ modulated by cross relaxation processes. Abstract : β-PbF2 :Tm 3+ /Yb 3+ glass ceramics (GCs) with varied Tm 3+ doped concentrations were synthesized by the conventional melting-quenching method and the subsequent glass crystallization route. For the first time, the lifetime-based thermometer based on up-conversion luminescence (UCL) originating from the 1 G4 state excited upon a miniaturized 976 nm diode laser excitation in β-PbF2 :Tm 3+ /Yb 3+ GCs is achieved. Furthermore, the thermosensitivity of the 1 G4 state lifetime is realized by the phonon-assisted cross relaxation (CR) processes between Tm 3+ which depopulate the 1 G4 state and get severer with temperature. The relative sensitivity ( S R ) of the 1 G4 state lifetime is promoted by intensifying CR processes via raising Tm 3+ concentration in this work. The maximum values of S R of 1 G4 state lifetime obtained in 0.0005Tm, 0.01Tm and 0.05Tm are 0.16%K −1, 0.26%K −1, and 0.46%K −1 at 488 K, respectively, which indicates the potential ability of Tm 3+ -doped nanoparticles to work as indicators for UCL lifetime-based thermometers.